Effects and mechanisms of fermentation media on sensory qualities, nonvolatile components, and microbiota in cigar tobacco leaves - Zhang, Qianying; Liu, Jie; Chai, Zhishun; Yang, Shuanghong; Jia, Yun; Zhang, Hongfei; Ji, Xiaoying; Lei, Jinshan; Li, Dongliang (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMedium fermentation is crucial for improving the quality and industrial value of cigar tobacco leaves (CTLs); however, its effect varies by variety. This study examined two CTLs (Dexue No. 1 from Shifang, Sichuan Province, and Chuxue No. 14 from Enshi, Hubei Province) using three fermentation media.MethodsThe effects that different media have on the sensory quality, chemical composition, microbial communities, and metabolism of CTLs were explored to reveal the mechanisms underlying quality differences.ResultsResults indicated that the effect different fermentation media have on the same type of CTL was less pronounced than that which a single medium had on different CTLs. The use of fermentation media altered the nonvolatile components and microbiota of the CTLs. Specifically, fermentation reduced the total polyphenol, neochlorogenic acid, and scopoletin content in Enshi CTLs, but increased the total amino acid and polyphenol content, including threonine, alanine, proline, and cryptochlorogenic acid, in Shifang CTLs. Among the six dominant microbes identified, only Staphylococcus was more abundant in Enshi CTLs than in Shifang CTLs, whereas Ralstonia, Pseudomonas, Aspergillus, Terribacillus, and Brachybacterium exhibited the opposite trend. Fermentation reduced the populations of R. pseudosolanacearum, R. solanacearum, and P. psychrotolerans in Shifang CTLs. A total of 18 genera, including Staphylococcus and Pseudomonas, contributed to the accumulation of 16 nonvolatile chemical components via carbohydrate and amino acid metabolism. Ultimately, this led to an enhancement in sensory attributes of the CTLs. Analysis of the metabolic network of phenylalanine, proline, and serine further confirmed that Staphylococcus played an important role in the metabolism of these three amino acids.ConclusionBoth fermentation medium and production area characteristics jointly influenced CTLs quality.